Computer-supported collaborative work (CSCW) in biomedical signal visualization and processing. - Bouillon, Y. (IEEE Transactions on information technology in biomedicine)
A collaborative extension to a platform dedicated to signal visualization and processing is presented. The platform now allows geographically distant users to work together, in real time, on the same data (electroencephalographic signals). The extension is based on a client-server collaborative architecture using remote procedure call programming. Through this first implementation, general issues of computer-supported collaborative work are presented.